Heterogeneity in Hydrocarbon and Organic Mater Distribution Patterns in the Offshore West Baram Delta, Sarawak Basin - Ben-Awuah, Joel; Padmanabhan, E. (Springer, 2017)
The objective of this paper was to evaluate heterogeneities in hydrocarbon and organic matter distribution patterns in the offshore West Baram Delta. A total of 170 samples from seven subsurface wells in the delta have been analyzed using FTIR and UV–Vis spectroscopy, and total organic carbon analyzer. Samples from wells W1, W6, and W3 show the lowest TOC values with averages of <1% indicating organic matter oxidation in these wells. The plot of E4 against E6 for samples from the four different fields shows a strong linear correlation between the two parameters. Such linear relationship between E4 and E6 suggests a fairly consistent supply of organic carbon into the environment during deposition. Generally, the farthest field offshore, i.e., Field C, has the highest E4/E6 ratios averaging 1.37 and decreasing to the most proximal field, i.e., Field A with an average of 1.24 suggesting a depositional environment control on the quality of the organic matter as well. The relative amount of aromatic functional groups generally increases from the samples nearest to the shoreline to the samples farther offshore, whereas the amount of aliphatic functional groups decreases from the nearshore to farther offshore samples. An overlay of the distribution of E5 across the wells shows similar distribution pattern to the aliphatic functional groups. Since a good relationship exists between these two parameters, it indicates that with knowledge on E5 values, hydrocarbon functional groups distribution can be predicted with a good degree of accuracy.